SWOT STRATEGY "UMKM GADO-GADO PAK KIRUN JEMBER" IN FACING BUSINESS COMPETITION - Yuliani, Dien; Mufidah, Hayatul; Dharma, Rendra Adi; Qomariah, Nurul (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
One of the businesses that supports the national economy that cannot be underestimated is Micro, Small and Medium Enterprises (MSMEs). The important roles that MSMEs can contribute include creating jobs, increasing people's income, and encouraging national economic growth. MSMEs have proven to be resilient when facing the monetary crisis that hit Indonesia. So that MSMEs can survive in the face of increasing business competition, the government has an important role in helping MSMEs to develop and become stronger. Cooperation and synergy is needed between the two parties, namely the government and MSMEs, so that the national economy can be strong and resilient. The purpose of this research is to find out how the marketing strategy carried out by "UMKM Gado-gado Pak Kirun Jember" increases sales. The type of research is qualitative with SWOT analysis. Data collection methods are interviews, documentation and observation. The results of this research show that the strategic analysis carried out has been effective and the SWOT strategy has been applied to increase sales at Gado-gado Pak Kirun UMKM, namely its advantages in the form of a distinctive sweet and spicy savory taste, prioritization of product quality, fast service, and a complete menu level of nutrients. with varying spiciness. Relatively affordable price. High nutritional value of gado-gado.